Experience of Surgical Treatment of Mitral Valve Pathology in Children - Maistriuk, Hanna V.; Dziuryi, Ivan V.; Truba, Iaroslav P. (Ukraïnsʹkyĭ z︠h︡urnal sert︠s︡evo-sudynnoï khirurhiï, 2025)
Isolated congenital mitral pathology occurs with a frequency of 0.5% among all congenital heart defects and is combined with others in 65–82% of cases. Surgical treatment of congenital mitral valve dysfunction still results in a significant mortality rate. In the presence of severe mitral valve pathology and the impossibility of performing valve repair in children of all ages, valve replacement becomes vitally necessary. The goal of mitral valve repair is not only to restore anatomy but, more importantly, to restore functional hemodynamics.     Аim. To analyze the perioperative characteristics of patients and the immediate and long-term results of surgical correction of the mitral valve in pediatric patients.    Materials and methods. Between 2014 and 2024, 135 patients aged 2 months to 18 years with congenital mitral valve anomalies underwent surgical correction (mitral valve repair or replacement) at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. There were 64 male patients (47.4 %) and 71 female patients (52.6 %). The most common congenital heart defects associated with mitral valve anomalies in the study group were: atrioventricular septal defect – 61 cases (45.2 %), hypertrophic cardiomyopathy – 24 (17.8 %), congenital isolated mitral valve disease – 15 (11.1 %), and infective endocarditis of the mitral valve – 10 (7.4 %).                    Results and discussion. In the early postoperative period, 4 patients died, resulting in a hospital mortality rate of 3.0 %. In 3 patients (2.2 %), the cause of death was acute heart failure, while in 1 patient (0.7 %) it was respiratory failure due to viral pneumonia. During long-term follow-up, there was one additional death (0.7 %).Mitral valve replacement was required in 6 patients (4.4 %). The mean follow-up duration was 49 ± 16.2 months. Severe residual mitral regurgitation occurred in 4 patients (2.3 %), necessitating reintervention. Moderate mitral regurgitation was observed in 22 patients (17 %), mild in 27 patients (20 %), and minimal in 32 patients (23.7 %). No recurrences were recorded among patients with infective endocarditis during the follow-up period. All patients with associated intracardiac anomalies underwent concomitant surgical correction.                    Conclusions. Modern diagnostic techniques enable the early detection of mitral valve anomalies, and contemporary surgical approaches yield favorable outcomes. Mitral valve repair is intended not only to reconstruct anatomical integrity but, more critically, to restore physiological hemodynamic performance. The 10-year reoperation-free rate of 97.1 % highlights the durability of surgical interventions. Reconstructive surgery remains the treatment of choice in pediatric patients, as it is associated with a lower risk of complications compared to valve replacement.